PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF DAN PRESTASI BELAJAR PESERTA DIDIK (Studi pada Mata Pelajaran Kimia Kelas X MIPA SMA Negeri 4 Pagar Alam - Tri Suhartiningsih; Bambang Sahono (UNIB Press, 2021)
This study aims to describe the application of the discovery learning model in improving the creative thinking skills and learning achievement of students and to describe the effectiveness of the application of the discovery learning model in improving the learning achievement of students in Chemistry subjects. This type of research is classroom action research (PTK) and quasi-experimental using a pre-test and post-test control group design. The study population was students of class X MIPA at SMA Negeri 4 Pagar Alam in the academic year 2020/2021. The research subjects were randomly selected by students of class X MIPA1 as the PTK class, X MIPA 2 as the experimental class and X MIPA 5 as the control class. Data collection techniques in this study used observation sheets to measure the learning process and creative thinking abilities of students and tests to measure learning achievement. While data analysis used average score analysis, normality test, homogeneity test and t-test. The results showed that: (1) the implementation of discovery learning models can improve students' creative thinking skills; (2) the aimplementation of discovery learning models can improve student achievement; (3) the application of discovery learning models effectively improves students' learning achievement